Transgender Representation in Bangladeshi Film: An Analysis of the Film Common Gender (Social Science Review, 2022)
This research has done to know how transgender people are represented in Bangladeshi film. Research found that transgender people are highly misrepresented in film and for this misrepresentation- they have to pay to achieve their rights from society. Hence, to work for the betterment of the transgender community in Bangladesh; it is important to know their representation style in Bangladeshi film. This paper has analysed the film Common Gender based on the content analysis method and the film narratology method while the representation theory worked as its theoretical framework. This paper found the film has represented transgender people in the same way that the Bangladeshi dominant society thinks about transgender people. There are no differences between the representation style and the reality. Hence, it can be argued that Bangladeshi films are influenced by the Bangladeshi dominant culture and transgender people have to pay to achieve their rights from society.Social Science Review, Vol. 38(1), June 2021 Page 69-92